OECD handbook on economic globalisation indicators (OECD, 2005)
This manual provides guidance on how to measure and interpret measurements of globalization's extent and intensity. The manual defines concepts and puts forward guidelines for data collection and fine-tuning of globalization indicators. In particular, it looks at indicators related to foreign direct investment, the economic activities of multinational enterprises, the internationalization of technology, and trade globalization.--Publisher description.